Substance use and suicide outcomes among self-injured trauma patients. (1st September 2021) - Karnick, Aleksandr T.; Caulfield, Nicole M.; Bauer, Brian W.; Martin, Rachel L.; Kaufman, Elinore J.; Winchell, Robert; Capron, Daniel W.
Highlights: Among trauma admissions for suicide, high BAC is associated with reduced mortality. Suicide patients with alcohol and substance use disorders had longer length of stay but reduced mortality. Acute drug use had no significant effect on mortality. Behavioral effects of substance use may reduce suicide capability in a given attempt. Prevention efforts should target substance users who may be at higher risk of eventual death by suicide. Abstract: Background: Research indicates alcohol (AUD) or substance (SUD) use disorders and acute alcohol or drug use serve as risk factors for suicidal behaviors and death both distally and proximally to a suicidal event. However, limited research has investigated these relationships among medically serious suicide attempters at the time of injury without relying on cohorts of substance users only or by examining suicide decedent characteristics. Methods: Data were collected from the National Trauma Data Bank (NTDB) for 2017. The sample comprised patients who engaged in suicidal and self-injurious acts that were medically serious enough to require trauma admission and were tested for alcohol (N = 9, 196) or drug (N = 8, 121) exposure upon admission. Logistic regression determined relationships between acute alcohol/substance use, presence of AUDs and SUDs and suicide mortality risk, while linear regression evaluated substance conditions and injury severity and length of stay (LOS). Results: AUDs (OR = 0.59[0.42−0.83]) and SUDs (OR = 0.66[0.48−0.90]) had reduced odds of death but increased LOS (β = 1.7, p < .001; β = 0.82, p = .024). Blood alcohol concentration (BAC) was positively associated with reduced odds of death (OR = 0.20[0.06−0.61]), injury severity (β = −5.3, p < .001), and LOS (β = −7.5, p < .001). Presence of cocaine (β = −0.80, p = .044) and opioids (β = −1.4, p < .001) were associated lower injury severity, while MDMA (β = 3.6, p = .016) and methamphetamine (β = 1.5, p = .025) were associated with increased injury severity. Conclusions: While higher BAC may be associated with lower odds of mortality during a single high-risk suicide event, substance users may be at increased risk for worse outcomes over time. Targeted interventions should be considered to interrupt and develop healthy alternatives for survivors with substance use conditions.